Criminal remedies of anti-doping security provision - Vladimir Petrovich Vaskevich, Ainur Gabdulbarovna Demieva,; Yuryevna Larina, Lyubov; Iroshnikov, Denis Vladimirovich (Opción, 2019)
The article analyzes the experience of legislative regulation of criminal liability for doping crimes in France, Germany, Italy and Russia via the dialectical method of scientific knowledge. As a result, it is also necessary to provide liability for the use of substances that can hide the use of doping. The authors come to the conclusion that the establishment of criminal liability for the use of doping by an athlete him-/herself is impractical since this act is not socially dangerous.